Two new species of the pseudoscorpion genus Stenohya (Pseudoscorpiones: Neobisiidae) from Guangxi Zhuang Autonomous Region, China - Li, Yun-Chun; Shi, Ai-Min (Zootaxa, 2023)
Two new pseudoscorpion species, Stenohya dongtianensis sp. nov. and S. jiahensis sp. nov., from Guangxi Zhuang Autonomous Region, are described and illustrated. An identification key is provided for all known representatives of the genus Stenohya from China.